2020
DOI: 10.3390/vaccines8020211
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza Vaccines: What did We Learn from the 2009 Pandemic and are We Better Prepared Now?

Abstract: In 2009, a novel A(H1N1) influenza virus emerged with rapid human-to-human spread and caused the first pandemic of the 21st century. Although this pandemic was considered mild compared to the previous pandemics of the 20th century, there was still extensive disease and death. This virus replaced the previous A(H1N1) and continues to circulate today as a seasonal virus. It is well established that vaccines are the most effective method to alleviate the mortality and morbidity associated with influenza virus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…Among these, MDCK and MDCK-SIAT1 cell lines are commonly used as they are highly permissive to influenza viruses, easy to cultivate and progeny virus contain few modifications from the OCS 9 . Currently, the majority of influenza virus vaccines are still manufactured in embryonated hen’s eggs 17 , 18 , although alternative non-egg host systems, such as the use of mammalian cells and recombinant protein vaccines have been licensed (reviewed in ref. 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, MDCK and MDCK-SIAT1 cell lines are commonly used as they are highly permissive to influenza viruses, easy to cultivate and progeny virus contain few modifications from the OCS 9 . Currently, the majority of influenza virus vaccines are still manufactured in embryonated hen’s eggs 17 , 18 , although alternative non-egg host systems, such as the use of mammalian cells and recombinant protein vaccines have been licensed (reviewed in ref. 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the current global influenza vaccine production capacity, it is unlikely that there would be sufficient vaccine available in the first 12 months of an influenza pandemic to meet global needs. Production capacities to provide a monovalent inactivated influenza vaccine at 15 μg HA per dose, as currently used in seasonal influenza vaccines, are estimated at 4 to 6 billion doses [ 11 , 12 ]. A study from the 2009 swine flu pandemic showed that eight months after the first detection of the virus, less than 500 million doses of monovalent vaccine of any sort were produced [ 13 ], which would have been woefully insufficient in the case of a pandemic of higher severity.…”
Section: Pandemic Influenza Vaccine Developmentmentioning
confidence: 99%
“…Consequently, there is still a need for the improvement of existing pandemic influenza vaccines. Novel egg-independent technologies are still very much in progress today, although they have started to be implemented for seasonal vaccines in certain parts of the world [ 12 , 14 , 16 ]. It is however questionable if some of these technologies could be implemented in LMICs on a large scale and within a suitable timeframe, in the case of a new rapidly spreading pandemic.…”
Section: Pandemic Influenza Vaccine Developmentmentioning
confidence: 99%
“…Current vaccines usually induce strain-specific immunity, and they can be ineffective if there is a mismatch between the circulating viruses and vaccine strains [ 111 ]. In addition, these vaccines usually do not confer protection against emergent pandemic strains, such as the H1N1 in 2009, for which production of a strain-specific vaccine became necessary [ 112 ]. Limitations of seasonal influenza vaccines and the constant threat of a new influenza pandemic urge for the development of a wider range of strategies to tackle these viruses.…”
Section: Aav Vectors Expressing Nanobodies To Fight Viral Infectionsmentioning
confidence: 99%